The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1021/acs.cgd.3c00151
|View full text |Cite
|
Sign up to set email alerts
|

Titanium Sulfonate-Based Metal–Organic Frameworks

Abstract: Titanium-based metal−organic frameworks (Ti-MOFs) are one of the most active fields of MOFs due to their intriguing catalytic properties; however, the fast reaction between the widely used carboxylate-based ligand (hard base) and Ti 4+ ion (hard acid) makes the syntheses of Ti-MOFs extremely challenging. In this work, we propose a new strategy by adopting sulfonic acid (soft base) as organic ligands to synthesize Ti-MOFs based on hard and soft acid and base (HSAB) theory. As an example of this strategy, seven … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 39 publications
(47 reference statements)
0
4
0
Order By: Relevance
“…Metal–organic frameworks (MOFs), 21 due to their large internal surface area, 22 flexibility in designing the active sites, 23 chemical alteration, 24 pore structure, and high metal content, 25 provide valuable opportunities to design compounds with multiple applications. 26 MOFs are less thermally and chemically stable compared to porous mineral solids, even though some of them decompose when exposed to air or moisture.…”
Section: Introductionmentioning
confidence: 99%
“…Metal–organic frameworks (MOFs), 21 due to their large internal surface area, 22 flexibility in designing the active sites, 23 chemical alteration, 24 pore structure, and high metal content, 25 provide valuable opportunities to design compounds with multiple applications. 26 MOFs are less thermally and chemically stable compared to porous mineral solids, even though some of them decompose when exposed to air or moisture.…”
Section: Introductionmentioning
confidence: 99%
“…8 Among MOFs, titanium-based metal–organic frameworks (Ti-MOFs) have garnered special attention due to their excellent photocatalytic activity. 9–21 Nevertheless, the scarcity of Ti-MOFs has limited the research in this area, with the focus mainly on two Ti-MOFs (MIL-125 and MIL-125-NH 2 ) reported over ten years ago. 22–24 Therefore, there is an urgent need to synthesize new Ti-MOFs.…”
Section: Introductionmentioning
confidence: 99%
“…As a new sort of functional porous materials, metal–organic frameworks (MOFs) or porous coordination polymers (PCPs) are well-known for their highly designable, large surface areas, and porous structures, which play an important role in numerous applications, such as gas storage, adsorption, separation, fluorescence sensing, etc. A lot of MOFs have been applied in the removal or detection of pollutants. For example, [Al­(OH)­(tdc)], [Zr 6 ( μ 3 -O) 6 ­( μ 3 -OH) 2 ­(tdc) 4 ­(OH) 2 ­(HCOO) 2 ], and [Ce 6 ­( μ 3 -O) 4 ­( μ 3 -OH) 4 ­(tdc) 4 ­(OH) 4 ­(H 2 O) 4 ], based on the functional H 2 tdc (2,5-thio­phene­di­carb­oxylic acid) ligand, exhibited efficient removal of fluoride .…”
Section: Introductionmentioning
confidence: 99%